Efficient and stable one-dimensional photonic crystal ultraviolet protective film and preparation method thereof

By alternately stacking the low-refractive index layer and high-refractive index layer hybridized by hollow SiO2 and silicone on a transparent polymer substrate, the stability and transparency of the ultraviolet reflective film layer in complex environments is solved, and an efficient ultraviolet protection effect is achieved.

CN120535795APending Publication Date: 2025-08-26ZHENGZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510652543.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-01
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing ultraviolet reflective one-dimensional photonic crystal film layers have poor stability in complex environments, and are difficult to take into account both reflectivity and transparency. They are prone to cracking, peeling and reduced transparency when applied on polymer substrates.

Method used

The low-refractive index layer and high-refractive index layer hybridized by hollow SiO2 and silicone are alternately stacked on the transparent polymer substrate to form a one-dimensional photonic crystal structure. The ultraviolet protective film is prepared in combination with the spin coating method to ensure high UV reflectivity and good adhesion.

Benefits of technology

It has achieved high reflectivity of 60%-90% in the 290-380nm band and high transparency of 380-780nm band. The ultraviolet reflectivity and visible light transmittance will not exceed 5% under long-term ultraviolet radiation. It is suitable for transportation, construction, aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535795A_ABST
    Figure CN120535795A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient and stable one-dimensional photonic crystal ultraviolet protective film and a preparation method thereof, and belongs to the technical field of protective films.The ultraviolet protective film comprises high-refractive-index layers and low-refractive-index layers which are alternately stacked on the surface of a transparent polymer substrate to form a multi-layer film of a one-dimensional photonic crystal (1DPhC for short) periodic structure, the core is that the low-refractive-index layer is made of a hybrid material of hollow SiO2 and organic silicon, so that the ultralow refractive index is realized, and the refractive index difference between the low-refractive-index layer and the high-refractive-index layer is enhanced. The efficient and stable ultraviolet protective film layer provided by the invention can realize high reflectivity of an ultraviolet wave band (for example, the average reflectivity of 290-380nm is 60%-90%) and high transmittance of a visible light wave band (for example, the transmittance of 380-780nm is greater than or equal to 80%) under the condition of a small number of stacked layers, and has excellent ultraviolet radiation stability, adhesion performance and environmental stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective films, and more specifically, to a highly efficient and stable one-dimensional photonic crystal ultraviolet protective film and a preparation method thereof. Background Art

[0002] Transparent polymers such as polycarbonate (PC) and polymethyl methacrylate (PMMA) are prone to aging and degradation under ultraviolet radiation, causing yellowing, embrittlement and other problems, which seriously restricts their service stability and service life in outdoor scenarios (such as transportation, construction, etc.) as well as aerospace, national defense and other fields.

[0003] One-dimensional photonic crystals (1DPhC) are periodic multilayer films formed by alternating layers of materials with different refractive indices. Based on the principle of optical interference, they can achieve selective reflection of specific wavelengths (also known as photonic bandgap). Through appropriate material selection and structural design, the optical transmission properties of 1DPhC can be manipulated to extend the photonic bandgap into the ultraviolet range without affecting the transmission of visible light. Existing research data indicates that 1DPhC has been applied in the field of transparent UV protection. Compared with traditional UV-absorbing films, 1DPhC avoids the volatilization, migration, and degradation issues associated with organic absorbing materials (such as benzophenones and salicylates), while also preventing the secondary effects of inorganic absorbing materials (such as ZnO and CeO2), such as decreased transparency and photocatalytic degradation. In summary, UV-reflective 1DPhC has great potential and market value for UV protection of transparent plastic parts such as automotive windshields and aerospace windows.

[0004] At present, according to the type of assembled unit layer materials, UV reflective 1DPhC films can be roughly divided into the following two categories: (1) Inorganic material systems, such as TiO2 / SiO2, HfO2 / SiO2, Si x N y / SiO2, etc. However, this type of 1DPhC film is brittle and has poor mechanical compatibility with the polymer substrate. It is prone to cracking, peeling and other problems, and the stability of the film in complex environments is difficult to guarantee; (2) Organic-inorganic hybrid material system, such as Junli Zhang et al. (see Journal of Materials Chemistry C.9(12).2021) modified TiO2 and SiO2 nanoparticles with organosilane to prepare UV-reflective 1DPhC film. Although the stability of the film is improved due to the increase of organic components, the refractive index contrast between adjacent film layers continues to decrease, resulting in the weakening of the interlayer interface reflection. The highest reflectivity in the UV band is only 70%. Therefore, it is crucial to develop a surface protective film suitable for transparent polymer substrates that has both high UV reflectivity and high stability. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a high-efficiency and stable one-dimensional photonic crystal UV protective film and a preparation method thereof, which has broad application prospects and extremely high market value in the fields of transportation, construction, aerospace, etc.

[0006] To achieve the above object, the present invention provides the following technical solutions: A highly efficient and stable one-dimensional photonic crystal UV protective film, comprising a high refractive index layer, a low refractive index layer, and a transparent polymer substrate. The high refractive index layer and the low refractive index layer are alternately stacked on the surface of the transparent polymer substrate to form a one-dimensional photonic crystal periodic structure multilayer film. The low refractive index layer is made of a hybrid of hollow SiO2 and organic silicon. The average reflectivity of the UV protective film in the 290-380nm UV band ranges from 60% to 90%; The transmittance of the ultraviolet protection film in the visible light band of 380-780nm is greater than or equal to 80%.

[0007] The present invention is further configured such that: the low refractive index layer serves as the first layer in direct contact with the transparent polymer substrate.

[0008] The present invention is further configured as follows: the adhesion of the protective film base reaches 5B, and after ultrasonic testing with solvents such as water, ethanol, and isopropanol, the decrease in ultraviolet reflectivity does not exceed 5%, after high and low temperature cycle testing at -50°C to 50°C, the decrease in ultraviolet reflectivity does not exceed 5%, after wet and hot cycle testing, the decrease in ultraviolet reflectivity does not exceed 5%, and after artificial accelerated medium-wave ultraviolet irradiation (main wavelength 313nm) for 240 hours, the decrease in visible light transmittance and ultraviolet reflectivity does not exceed 5%.

[0009] The present invention is further configured as follows: the protective film has an ultraviolet reflectivity of 72.53% at a central wavelength of 335nm, and the half-width of the reflection spectrum is 105nm, that is, the band gap range is 280-385nm. Under this condition, wide-band blocking of medium-wave (UVB) and long-wave ultraviolet (UVA) is achieved simultaneously.

[0010] The present invention is further configured as follows: the ultraviolet reflectivity of the protective film reaches 88.91% at a central wavelength of 365nm, the half-width of the reflection spectrum is 125nm, that is, the band gap range is 310-435nm, and the average visible light transmittance reaches 81.8%. Under this condition, deep blocking of long-wave ultraviolet rays is achieved.

[0011] A method for preparing a highly efficient and stable one-dimensional photonic crystal UV protective film, the steps of which are as follows: S1. Preparation of solution for low refractive index layer Take isopropyl alcohol (IPA) and place it in a beaker, then slowly add methyltrimethoxysilane (MTMS), and then add deionized water dropwise, stir and react for 10-30 minutes, then add a small amount of glacial acetic acid to promote the hydrolysis of MTMS, stir and react at room temperature for 30-60 minutes, then add γ-glycidyloxypropyltrimethoxysilane (GPTMS), continue stirring for 10-30 minutes, then add a small amount of concentrated HCl to promote the hydrolysis of GPTMS, stir and react at room temperature for 36-48 hours, and finally add a certain amount of tetrabutylammonium hydroxide as a curing agent. After completion, let it stand and age for 18 hours for use, and mix the hollow SiO2 aqueous dispersion with the above-mentioned silicone solution to obtain a hollow SiO2 / silicone hybrid system, the volume ratio of hollow SiO2 to silicone is 7:3, and the mass fraction of hollow SiO2 is 2wt%; S2. Preparation of solution for high refractive index layer The mass fraction of the TiO2 solution used to prepare the high refractive index layer is preferably controlled to 1.5wt%; Isopropyl alcohol and tetrabutyl titanate are sequentially added to a container and stirred for 10-20 minutes, and then a mixture of deionized water, concentrated hydrochloric acid (37%) and isopropyl alcohol is added dropwise to the container at a rate of preferably 1-2 drops per second. The mixture is stirred at room temperature for 1-3 hours to obtain a TiO2 sol after the reaction is completed. S3. Preparation of UV protective film; A low refractive index layer is coated on the substrate at a spin coating speed of 3000-4000 rpm for 20-60 seconds, dried at 60-90°C for 20-30 minutes, and then a high refractive index layer is coated at a spin coating speed of 3000-4000 rpm. The coating is then dried and cured at 50-70°C for 10-20 minutes. The above process is repeated 3-4 times.

[0012] The present invention is further configured as follows: the volume ratio of each substance in S1 is as follows: IPA 10-20 parts, MTMS 15-30 parts, GPTMS 0.4-1 part, deionized water 14-28 parts, glacial acetic acid 0.1-0.5 parts, trace amounts of concentrated hydrochloric acid and tetrabutylammonium hydroxide, wherein isopropyl alcohol can also be replaced by ethanol or methanol.

[0013] The present invention is further configured as follows: the mass ratio of each substance in S2 is as follows: 10-20 parts of isopropyl alcohol, 3-10 parts of tetrabutyl titanate, 1-3 parts of deionized water, and a trace amount of concentrated hydrochloric acid. Isopropyl alcohol can also be replaced by ethanol or methanol.

[0014] The advantages of the present invention are: The present invention provides a highly efficient and stable UV protective film layer on the surface of a transparent polymer, which can achieve high reflectivity in the UV band while maintaining high transmittance in the visible light band with a small number of required stacked layers. The selected material systems all have high UV stability and do not cause significant degradation of the optical performance of the film layer due to long-term UV irradiation. The preparation process is simple, and a highly reflective one-dimensional photonic crystal multilayer film can be obtained without additional treatment. It has good adhesion and environmental stability, and the materials used are non-toxic and harmless. Compared with traditional coating methods, it can significantly reduce costs and can be applied to the field of UV protection of transparent polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the structure and optical properties of the UV protective film of the present invention; Figure 2 (a) Schematic diagram of the structure of a 1DPhC UV protective film according to Example 1 of the present invention, (b) a graph showing the variation of the refractive index n and extinction coefficient k of the high and low refractive index layers with wavelength, and (c) a graph showing the reflectance spectrum of the protective film; Figure 3 (a) Schematic diagram of the structure of the 1DPhC UV protective film and (b) reflection and transmission spectra of Example 2 of the present invention; Figure 4 (a) Schematic diagram of the structure of the 1DPhC UV protective film and (b) a cross-sectional scanning electron microscope image of Example 3 of the present invention; Figure 5 This is the reflection and transmission spectra of the 1DPhC UV protective film according to Example 3 of the present invention; Figure 6 (a) Changes in the yellowing index of PC and 1DPhC / PC under artificial accelerated medium-wave ultraviolet irradiation, (b) Changes in the average visible light transmittance of PC and 1DPhC / PC, and (c) Changes in the peak reflectivity of 1DPhC / PC of Example 3 of the present invention; Figure 7 (a) Schematic diagram of 1DPhC / PC adhesion test and (b) rating criteria and surface morphology diagram of Example 3 of the present invention; Figure 8 (a) Schematic diagram of the high and low temperature cycle test of Example 3 of the present invention, (b) graph showing the change in peak reflectivity of 1DPhC UV protection film, and (c) transmittance spectra before and after the test; (d) schematic diagram of the wet heat cycle test, (e) graph showing the change in peak reflectivity of 1DPhC UV protection film, and (f) transmittance spectra before and after the test; Figure 9 This is a graph showing the change in peak reflectivity of 1DPhC / PC under a solvent ultrasonic environment in Example 3 of the present invention. DETAILED DESCRIPTION

[0016] See also Figure 1-9 , the present invention provides the following technical solutions: Specifically, it refers to a highly efficient and stable one-dimensional photonic crystal UV protective film, which is characterized by comprising a 1DPhC structure formed by alternating stacking of low-refractive index layers and high-refractive index layers made of hollow SiO2 and organic silicon hybrid on a transparent polymer substrate.

[0017] Among them, the spin coating method can also be replaced by other solution processing methods such as dip coating, flow coating, and spray coating.

[0018] Furthermore, since the low-refractive-index material is hybridized by organic silicon with excellent stability and hollow SiO2, compared with the existing technology, the low-refractive-index material has a lower refractive index, forming a high refractive-index difference with the high-refractive-index material, thereby ensuring that 1DPhC achieves high reflection in a wide band and ensures the effectiveness of the UV protective film.

[0019] Furthermore, the high refractive index layer material includes: titanium dioxide, hafnium oxide, tantalum oxide, aluminum oxide, zirconium oxide, and vanadium pentoxide.

[0020] Furthermore, the substrate may be selected from transparent polymer products such as polycarbonate (PC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), and polyimide.

[0021] Among them, the transparent polymer substrate needs to undergo but is not limited to plasma surface modification treatment before coating. During the treatment, the substrate is cleaned and placed horizontally on the sample stage in the plasma treatment chamber to ensure that the sample is exposed to the plasma glow. The plasma treatment power is set to 30-60W and the treatment time is 30-60s. After a certain vacuum degree is maintained in the chamber, the gas cylinder valve is opened and the plasma treatment program is started. The plasma surface modification method can also be replaced by other surface modification methods such as short-wave ultraviolet (UVC) irradiation and chromic acid etching.

[0022] The 1DPhC UV protective film applied for by the present invention has a reflectivity range of 60% to 90% in the 290-380nm band, which significantly reduces the aging rate of the polymer substrate; the average visible light transmittance exceeds 80%, ensuring the high transparency of the polymer substrate; after 240 hours of artificial accelerated medium-wave ultraviolet (main wavelength 313nm) irradiation, high and low temperature cycle test, wet heat cycle test and solvent ultrasonic test and other environmental tests, the decrease in UV reflectivity does not exceed 5%, showing excellent stability. It has broad application prospects and extremely high market value in the fields of transportation, construction, aerospace, etc.

[0023] The present invention designs a new technical solution based on the above scheme: Example 1 A method for preparing an efficient and stable one-dimensional photonic crystal UV protective film, the specific steps are as follows: S1, preparing a solution for a low refractive index layer; The water bath temperature was set to 28°C, 15.1 mL of methyltrimethoxysilane was dropped into 10 mL of isopropanol, and stirred for 10 min. 14 mL of deionized water was slowly added dropwise, and stirred for another 10 min. 0.5 mL of glacial acetic acid was added to promote the hydrolysis of MTMS. After stirring for 30 min, 3.9 mL of GPTMS was added dropwise, and stirring was continued for 10 min. Subsequently, 37 μL of concentrated hydrochloric acid (37%) was added to promote the hydrolysis of GPTMS. The mixture was stirred in a water bath stirred pot at 28°C for 48 h, and then aged for 18 h. Finally, 53 μL of tetrabutylammonium hydroxide (TBAOH) curing agent was added, and the mixture was stirred for 20 min to obtain an organosilicon solution with a mass fraction of 17.8 wt%. After the reaction was completed, the hollow SiO2 aqueous dispersion and the organosilicon solution were mixed and stirred for 20 min for use. The volume ratio of hollow SiO2 to organosilicon was 7:3. The film layer obtained later was recorded as SH70. S2, preparing a solution for a high refractive index layer; 7 mL of isopropyl alcohol and 5 mL of tetrabutyl titanate were added to a beaker in sequence and stirred for 10 min, which was recorded as solution A. 0.5 mL of deionized water and 40 μL of concentrated hydrochloric acid (37%) were added to 8 mL of isopropyl alcohol in sequence and mixed well, which was recorded as solution B. Solution B was added dropwise to solution A (1 drop / 3 s), and the mixture was reacted at 25°C for 2 h to obtain a TiO2 sol with a mass fraction of 6.8 wt%. After the reaction, the mixture was immediately diluted, sealed, and refrigerated for later use. S3, preparing a UV protection multilayer film; SH70 sol was diluted to 2wt% with anhydrous ethanol, and TiO2 sol was diluted to 1.5wt%. The PC was cleaned and dried, and then the PC substrate was treated with oxygen plasma at a processing power of 40W and a processing time of 30s to increase the hydrophilicity of its surface; SH70 sol was coated on the above PC at a spin coating speed of 3000rpm for 30s, and then placed in a blast oven at 80°C for 30min to dry, and then 1.5wt% TiO2 sol was coated at a spin coating speed of 3000rpm for 30s, and placed in a blast oven at 60°C for 15min to dry; the above coating process was repeated (no parameters were changed in subsequent coatings) 3 times.

[0024] The UV protection multilayer film of this embodiment is as shown in the attached specification. Figure 2 As shown in part (a), starting from the top of the substrate are low refractive index unit layer L1, high refractive index unit layer H1, low refractive index unit layer L2, high refractive index unit layer H2, low refractive index unit layer L3, high refractive index unit layer H3, a total of 6 layers and 3 periods. The refractive index n and extinction coefficient k of the high and low refractive index layers change with the wavelength of light, which can be seen in the appendix of the manual. Figure 2In part (b), the refractive index difference can reach 0.7, which helps 1DPhC achieve a strong reflection band at a smaller number of periods. In addition, the extinction coefficient of the high and low refractive index film layers is 0 in the visible light region of 400-780nm, which helps to achieve high transmittance in the visible light region.

[0025] The spectral characteristics of the UV protection multilayer film of this embodiment can be seen in the appendix of the specification. Figure 2 As shown in part (c), the central wavelength of the high reflection band is 335nm, the central wavelength reflectivity is 72.53%, the high reflection band range is 280-385nm, the average reflectivity in the ultraviolet band of 290-320nm (UVB) is 61.02%, and the average reflectivity in the ultraviolet band of 320-380nm (UVA) is 60.34%.

[0026] The ultraviolet protective film of this embodiment can simultaneously achieve wide-band blocking of UVB and UVA, and is suitable for radiation protection of transparent plastic products used in UVB and UVA environments in fields such as outdoor and aerospace.

[0027] Example 2 See the instructions attached Figure 3 , attached Figure 3 Part (a) is a schematic diagram of the structure of the long-wave ultraviolet protection multilayer film of this embodiment. The specific operation steps are as follows: S1. The preparation method of the high and low refractive index materials of the UV protection multilayer film of Example 2 is the same as that of Example 1, the low refractive index material is SH70, and the high refractive index material is TiO2; S2. During the preparation of the long-wave ultraviolet protection multilayer film of Example 2, the spin coating speed was set to 2000 rpm, the other process parameters were consistent with those of Example 1, and the number of layers of alternating spin coating was 8 (4 cycles).

[0028] The reflection and transmission spectra of the UV protection multilayer film of this embodiment are shown in the attached figure. Figure 3 As shown in part (b), further spectrum fitting revealed that the thickness of the low refractive index layer in Example 2 was 78 nm, and the thickness of the high refractive index layer was 40 nm. The spectral characteristics of the UV protection multilayer film prepared in this example are as follows: The central wavelength of the high reflection band is 365nm, the central wavelength reflectivity is 88.91%, the high reflection band range is 310-435nm, the average reflectivity in the long-wave ultraviolet band of 320-380nm is 84.85%, and the average transmittance of visible light reaches 81.8%.

[0029] The high-reflection band of the UV protection multilayer film of this embodiment completely covers the long-wave UV band, which can effectively shield the long-wave UV that is widely present in the surface environment. It is suitable for UV protection of transparent plastic products serving outdoors, and has great potential for application in automobile windshields, buildings, glasses, etc.

[0030] Example 3 See the instructions attached Figure 4-9 The UV protection multilayer film proposed in this embodiment refers to a periodic multilayer film prepared by alternating deposition of high and low refractive index materials on the substrate surface. Figure 4 The schematic diagram and cross-sectional morphology of the UV protection multilayer film of this embodiment are shown below. The preparation steps are as follows: S1. The preparation method of the high and low refractive index materials of the UV protection multilayer film of Example 3 is the same as that of Example 1, the low refractive index material is SH70, and the high refractive index material is TiO2; S2. The preparation process of the UV protection multilayer film of Example 3 is consistent with that of Example 1, with the number of alternating spin coating layers being 8 and the number of cycles being 4.

[0031] The reflection and transmission spectra of the UV protection multilayer film of this embodiment can be found in the appendix of the specification. Figure 5 As shown, the central wavelength of the high reflection band is 335nm, the central wavelength reflectivity is 90%, the high reflection band range is 290-400nm, the average reflectivity of the ultraviolet band of 290-320nm (UVB) is 78.48%, the average reflectivity of the ultraviolet band of 320-380nm (UVA) is 81.01%, and the average transmittance of visible light is 86%.

[0032] The ultraviolet protective film of this embodiment can simultaneously achieve wide-band deep blocking of UVB and UVA, and is very suitable for radiation protection of transparent plastic products used in UVB and UVA environments such as aerospace, and has great application value in the aerospace field.

[0033] The UV protection film of this embodiment effectively reduces the aging rate of the PC substrate. After 240 hours of artificial accelerated UVB aging (main wavelength 313nm), the yellowing index is used as the aging index (see Figure 6 a), the PC substrate protected by the UV protective film in this embodiment has a 30.31% lower aging rate and a 79.7% lower visible light transmittance decrease rate compared to the bare PC (see Figure 6 b); During this process, the peak reflectivity of the UV protective film of this embodiment remains unchanged (see Figure 6 c), achieving efficient and stable protection of polymer substrates.

[0034] In order to investigate the adhesion performance between the UV protection multilayer film and the PC substrate of this embodiment, the ASTM D3359 test standard was used. Figure 7 The cross-cut test and evaluation method shown in a are used to test the adhesion between 1DPhC and PC. Figure 7 As shown in Figure b, the edge of the scratch is clear and continuous, without any cracks or peeling. The adhesion rating is 5B, indicating good adhesion between 1DPhC and PC.

[0035] The present invention designs a series of environmental tests to evaluate the stability of the UV protective 1DPhC multilayer film, including high and low temperature cycling, wet heat cycling, friction and solvent ultrasonic testing.

[0036] High and low temperature cycle test: Figure 8 As shown in a, each cycle includes cooling from room temperature to -50°C and holding for 4 hours, then heating to 50°C and holding for 4 hours, and finally cooling to room temperature, for a total of 5 cycles. The peak reflectivity of the UV protection multilayer film of this embodiment decreases by no more than 5% during the cycle (see Figure 8 b), the transmittance spectrum remains consistent before and after the test (see Figure 8 c).

[0037] Humidity and heat cycle test: Figure 8 As shown in Figure d, each cycle includes cooling from room temperature to -2°C and maintaining it for 4 hours, and then heating to 40°C and maintaining it for 4 hours. During the heating and cooling stages, the humidity is always maintained above 80%, while during the high and low temperature stages, the humidity exceeds 94%. A total of 5 cycles are performed. The peak reflectivity of the UV protection multilayer film of this embodiment does not decrease by more than 5% during the cycle (see Figure d). Figure 8 e), the transmittance spectrum remains consistent before and after the test (see Figure 8 f).

[0038] Solvent ultrasonic test: The samples of this embodiment were placed in beakers containing water, ethanol, and isopropyl alcohol, respectively. The beakers were placed in an ultrasonic cleaning machine and treated for 120 minutes. The samples were taken out every 10 minutes to test the reflectivity, and the change in the maximum reflectivity was recorded. Figure 9 As shown, for the three types of solvents subjected to ultrasound, the peak reflectivity of the sample of this embodiment did not change by more than 1%; under this condition, the sample of this embodiment achieved excellent solvent stability.

Claims

1. A highly efficient and stable one-dimensional photonic crystal UV protective film comprising a high refractive index layer, a low refractive index layer, and a transparent polymer substrate, characterized in that: The high refractive index layer and the low refractive index layer are alternately stacked on the surface of the transparent polymer substrate to form a one-dimensional photonic crystal periodic structure multilayer film, and the low refractive index layer is made of hollow SiO2 and organic silicon hybrid; The average reflectivity of the UV protective film in the 290-380nm UV band ranges from 60% to 90%; The transmittance of the ultraviolet protection film in the visible light band of 380-780nm is greater than or equal to 80%.

2. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 1, characterized in that: The low refractive index layer serves as the first layer in direct contact with the transparent polymer substrate.

3. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 1, characterized in that: The protective film has a membrane base adhesion of 5B. After ultrasonic testing with solvents such as water, ethanol, and isopropyl alcohol, the decrease in ultraviolet reflectivity does not exceed 5%. After a high and low temperature cycle test at -50°C to 50°C, the decrease in ultraviolet reflectivity does not exceed 5%. After a wet and hot cycle test, the decrease in ultraviolet reflectivity does not exceed 5%. After artificial accelerated medium-wave ultraviolet irradiation (main wavelength 313nm) for 240 hours, the decrease in visible light transmittance and ultraviolet reflectivity does not exceed 5%.

4. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 1, characterized in that: The protective film has an ultraviolet reflectivity of 72.53% at a central wavelength of 335nm, and a half-width of the reflection spectrum of 105nm, that is, a band gap range of 280-385nm. Under this condition, it can simultaneously achieve wide-band blocking of medium-wave (UVB) and long-wave ultraviolet (UVA).

5. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 1, characterized in that: The protective film has an ultraviolet reflectivity of 88.91% at a central wavelength of 365nm, a half-width of the reflection spectrum of 125nm, that is, a bandgap range of 310-435nm, and an average visible light transmittance of 81.8%. Under these conditions, deep long-wave ultraviolet blocking is achieved.

6. A method for preparing a high-efficiency and stable one-dimensional photonic crystal UV protective film, based on the high-efficiency and stable one-dimensional photonic crystal UV protective film according to any one of claims 1 to 5, characterized in that: The operation steps are as follows: S1. Preparation of solution for low refractive index layer Take isopropyl alcohol (IPA) and place it in a beaker, then slowly add methyltrimethoxysilane (MTMS), and then add deionized water dropwise, stir and react for 10-30 minutes, then add a small amount of glacial acetic acid to promote the hydrolysis of MTMS, stir and react at room temperature for 30-60 minutes, then add γ-glycidyloxypropyltrimethoxysilane (GPTMS), continue stirring for 10-30 minutes, then add a small amount of concentrated HCl to promote the hydrolysis of GPTMS, stir and react at room temperature for 36-48 hours, and finally add a certain amount of tetrabutylammonium hydroxide as a curing agent. After completion, let it stand and age for 18 hours for use, and mix the hollow SiO2 aqueous dispersion with the above-mentioned silicone solution to obtain a hollow SiO2 / silicone hybrid system, the volume ratio of hollow SiO2 to silicone is 7:3, and the mass fraction of hollow SiO2 is 2wt%; S2. Preparation of solution for high refractive index layer The mass fraction of the TiO2 solution used to prepare the high refractive index layer is preferably controlled to be 1.5wt%; Isopropyl alcohol and tetrabutyl titanate are sequentially added to a container and stirred for 10-20 minutes, and then a mixture of deionized water, concentrated hydrochloric acid (37%) and isopropyl alcohol is added dropwise to the container at a rate of preferably 1-2 drops per second. The mixture is stirred at room temperature for 1-3 hours to obtain a TiO2 sol after the reaction is completed. S3. Preparation of UV protective film; A low refractive index layer is coated on the substrate at a spin coating speed of 3000-4000 rpm for 20-60 seconds, dried at 60-90°C for 20-30 minutes, and then a high refractive index layer is coated at a spin coating speed of 3000-4000 rpm. The coating is then dried and cured at 50-70°C for 10-20 minutes. The above process is repeated 3-4 times.

7. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 6, characterized in that: The volume ratio of each substance in S1 is as follows: 10-20 parts of IPA, 15-30 parts of MTMS, 0.4-1 part of GPTMS, 14-28 parts of deionized water, 0.1-0.5 parts of glacial acetic acid, a trace amount of concentrated hydrochloric acid and tetrabutylammonium hydroxide, wherein isopropyl alcohol can also be replaced by ethanol or methanol.

8. The high-efficiency and stable one-dimensional photonic crystal UV protective film according to claim 6, characterized in that: The mass proportions of the substances in S2 are as follows: 10-20 parts of isopropyl alcohol, 3-10 parts of tetrabutyl titanate, 1-3 parts of deionized water, and a trace amount of concentrated hydrochloric acid. Isopropyl alcohol can also be replaced by ethanol or methanol.